Reduction of Pain Episodes and Prothrombotic Activity in Sickle Cell Disease by Dietary n-3 Fatty Acids - Tomer, Aaron; Kasey, Suha; Connor, William E.; Clark, Scott; Harker, Laurence A.; Eckman, James R. (Thrombosis and Haemostasis, 2001)
The effects of dietary n-3 fatty acids (n-3FAs) on the frequency of pain episodes and ex vivo blood tests of thrombosis have been evaluated in patients with sickle cell disease (SCD) utilizing a doubleblind, olive oil-controlled clinical trial. Dietary n-3FA therapy (0.1 g/kg/d) was provided as menhaden fish oil (0.25 g/kg/d) containing 12% eicosapentaenoic acid (EPA), and 18% docosahexaenoic acid (DHA). Within 1 month dietary n-3FAs exchanged with n-6FAs in plasma and erythrocyte membrane phospholipids (p <0.01 in all cases).Treatment with dietary n-3FAs for 1 year reduced the frequency of pain episodes requiring presentation to the hospital from 7.8 events during the preceding year to 3.8 events/year (p <0.01; n = 5). By contrast, subjects receiving control dietary olive oil (n = 5) experienced 7.1 pain events/year, compared to 7.6 during the previous year (p >0.4). The reduction in episodes in n-3FA-treated subjects was also significant when compared to control subjects (p <0.01). Dietary n-3FA therapy was not associated with hemorrhagic, gastrointestinal or other adverse effects.Compared to 10 asymptomatic African-American controls, sickle cell subjects demonstrated significantly increased pretreatment: 1) flow cytometric expression of platelet membrane P-selectin (CD62p; p <0.01) and annexin V binding sites (p = 0.02); 2) plasma levels of platelet-specific secretory proteins platelet factor 4 (PF4) and -thromboglobulin (TG) (p <0.01 in both cases); 3) plasma products of thrombin generation, prothrombin fragment 1.2 (F1.2) and thrombin:antithrombin (TAT) complex (p <0.01 in both cases); and 4) plasma levels of thrombolytic products, D-dimer and plasmin:antiplasmin (PAP) complex (p <0.01 in both cases). Treatment with dietary n-3FAs concurrently decreased plasma levels of F1.2, D-dimer, and PAP (p <0.05, compared to olive oil controls), implying that the reduction in pain events was related to n-3FA-dependent inhibition of thrombosis. We conclude that dietary n-3FAs reduce the frequency of pain episodes perhaps by reducing prothrombotic activity in sickle cell disease.
Keywords: Sickle cell; thrombosis; n-3 fatty acids